2010
DOI: 10.1007/s11739-010-0387-4
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in iron metabolism and related disorders

Abstract: Iron is essential for life, because it is indispensable for several biological reactions such as oxygen transport, DNA synthesis and cell proliferation, but is toxic if present in excess since it causes cellular damage through free radical formation. Either cellular or systemic iron regulation can be disrupted in disorders of iron metabolism. In the past few years, our understanding of iron metabolism and its regulation has dramatically changed. New disorders of iron metabolism have emerged and the role of iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…Iron is stored in cells in the form of ferritin, which protects cells from its toxic effects and that iron is transported in plasma mainly bound to Tf. Nonheme iron is mostly absorbed in the duodenum where ferric iron (Fe 3+ ) in food is reduced to Fe 2+ by the cytochrome reductase DcytB and then transported across the apical membrane into the enterocyte by DMT1 [61]. The miRNA responsible for iron homeostasis in mice has been identified as the liver-specific miR-122 [62].…”
Section: Figure 7 Mechanism Involved In Internalization Of Alginate-mentioning
confidence: 99%
“…Iron is stored in cells in the form of ferritin, which protects cells from its toxic effects and that iron is transported in plasma mainly bound to Tf. Nonheme iron is mostly absorbed in the duodenum where ferric iron (Fe 3+ ) in food is reduced to Fe 2+ by the cytochrome reductase DcytB and then transported across the apical membrane into the enterocyte by DMT1 [61]. The miRNA responsible for iron homeostasis in mice has been identified as the liver-specific miR-122 [62].…”
Section: Figure 7 Mechanism Involved In Internalization Of Alginate-mentioning
confidence: 99%
“…In the general population microcytic anemia is typically associated with iron deficiency, secondary to poor oral intake, malabsorption or active bleeding, [4, 5] conditions that are not uncommon in patients with PMF. [6] Furthermore, iron homeostasis has been shown to be abnormal in patients with PMF.…”
Section: 0 Introductionmentioning
confidence: 99%
“…In addition, serum ferritin level is difficult to interpret during inflammation because its expression is induced by both iron overload and inflammatory cytokines [8]. Recently, it has been demonstrated that there is an expanded role of hepcidin in ACD, a hormone of iron metabolism, [21]. Although the application of the ratio of soluble transferrin receptor (sTfR)/ferritin in distinguishing ACD from ACD/IDA is suggested, it may be difficult to implement in everyday clinical practice [9].…”
Section: Discussionmentioning
confidence: 99%